2016
DOI: 10.1038/ncomms11128
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent mutator genotype identified in fungal pathogen Candida glabrata promotes multi-drug resistance

Abstract: The fungal pathogen Candida glabrata has emerged as a major health threat since it readily acquires resistance to multiple drug classes, including triazoles and/or echinocandins. Thus far, cellular mechanisms promoting the emergence of resistance to multiple drug classes have not been described in this organism. Here we demonstrate that a mutator phenotype caused by a mismatch repair defect is prevalent in C. glabrata clinical isolates. Strains carrying alterations in mismatch repair gene MSH2 exhibit a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
287
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(302 citation statements)
references
References 35 publications
(47 reference statements)
13
287
2
Order By: Relevance
“…FKS1 HS1 and FKS2 HS1 regions were amplified and sequenced in both directions as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
“…FKS1 HS1 and FKS2 HS1 regions were amplified and sequenced in both directions as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping showed that isolates were identical before and after micafungin progressive exposure, thus excluding any potential contamination of the isolates during the propagation steps. The emergence of echinocandin resistance could be caused by the predisposition of this pathogen to easily acquire mutations in response to drug pressure due to its haploid nature and to alterations caused by mismatched repair genes (15). The five isolates studied became echinocandin resistant when grown even on plates containing low concentrations of micafungin.…”
mentioning
confidence: 99%
“…Alterations in sterol-and phospholipid composition as well as changes in membrane structure account for different polyene-cross-resistance patterns [130,131] and were found in clinical isolates resistant to Azoles as well as polyenes [98,[132][133][134][135][136][137]. The situation is probably aggravated by the finding that a mutator phenotype caused by a mismatch repair defect is prevalent in C. glabrata [138]. This genetic mechanism promotes the acquisition of resistance to multiple antifungals.…”
Section: Cross Resistance Multidrug Resistance and Horizontal Gene mentioning
confidence: 99%